The Effect of Ischemic Stroke to Cognitive Disorders in RSUD Dr. Moewardi - Arwindya Galih Desvitarini; Subandi .; Dhoni Akbar Ghozali (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Stroke is the fourth highest cause of death in the world after heart disease, cancer, and chronic lower respiratory tract disease. In Indonesia, stroke is the major cause of death, covering about 15.4% of deaths. Damage to brain cells due to stroke may cause cognitive dysfunction. Two-thirds of stroke patients may reveal cognitive degradation in various domains such as attention, language, memory, executive function, and visuospatial ability. This study aimed to analyze the effect of ischemic stroke to cognitive disorders. Method: This was an observational analytic study with cross-sectional approach which was conducted from July to September2014 at Neurology Outpatient Clinicof RSUD Dr. Moewardi Surakarta. A total of 50 subjects were obtained by fixed exposure sampling. The data were retrieved by using MoCA-Ina questionnaire and interviewing the respondents. The data were analyzed by Chi Square test and multiple logistic regression using SPSS 20.0 program for Windows. Result: Three independent variables were analyzed, which consisted of ischemic stroke, age, and level of education. Ischemic stroke was the only independent variable that associated with cognitive disorders significantly (p = 0.010). There were no association with cognitive disorders found in both age (p = 0.279 and level of education (p = 0.074). Conclusion: There is a significant association between ischemic stroke and cognitive disorders. Keywords: Ischemic stroke, cognitive disorder, MoCA-Ina